Factors Influencing Decisions on Selecting Expedition Services in E-Commerce Shopee and Tokopedia - Zahra, Khairani; Ermawati, Wita Juwita; Hidayati, Nurul (BALANCE: Economic, Business, Management and Accounting Journal, 2024)
The increase in online shopping among the community has led to the use of courier services for shipping goods. However, on the other hand, the increased frequency and volume of shipments have caused various problems experienced by consumers related to deliveries that do not meet expectations. Starting from these issues,, the purposes of this study were: (i) to analyze the decision-making process for selecting e-commerce services by e-commerce’s consumers in West Java during the Covid-19 pandemic; (ii) to analyze the factors that influence customer decision making in choosing expedition service on e-commerce during the Covid-19 pandemic. This research was held in February – June 2022. The population of this study was the users of expedition services from e-commerce Shopee and Tokopedia in West Java. The sampling method used in this study was purposive sampling technique about 312 respondents. The data analysis technique used was descriptive analysis and SEM-PLS. The results showed that the decision-making process for the selection of expedition services on e-commerce in West Java during the Covid-19 pandemic was carried out through five stages, namely problem recognition, information search, alternative evaluation, purchase decisions, and post-use. Of the six factors that have been tested, there were only two factors that had a significant influence, namely customer trust and service quality. The implications of this study suggested expedition services companies to implicate factors that have been proven to be influential, namely customer trust and service quality into the 7P service marketing mix. In addition to the 7P marketing mix, expedition services companies can use blue ocean strategy, namely by eliminating-reducing-increasing-creating Keywords: decision making; expeditionary service; e-commerce; SEM-PLS